2021
DOI: 10.1155/2021/6619855
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture at the P6 Acupoint to Prevent Postoperative Pain after Craniotomy: A Randomized, Placebo-Controlled Study

Abstract: Objective. Acute pain management after craniotomy can be challenging. Previous studies have shown inadequate pain control following the procedure. Oral medication can sometimes be delayed by postoperative nausea, and use of anesthetics may impair the assessment of brain function. We conducted this prospective study to evaluate the effect of acupuncture at the P6 acupoint on postoperative pain, nausea, and vomiting in patients undergoing craniotomy. Methods. The authors conducted a randomized, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…( 6) How to avoid bias produced by acupuncture specificity remains to be addressed, and the criteria for acupuncture quantification are unclear. (7) rough the literature measurement tool, we can clarify the current research trend and the cross-research between disciplines and even countries, which is significantly beneficial to the research progress of acupuncture treatment of pain, but there are still deficiencies. e literature selected in this paper is in English, while other languages are not included, which may lead to bias in some aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 6) How to avoid bias produced by acupuncture specificity remains to be addressed, and the criteria for acupuncture quantification are unclear. (7) rough the literature measurement tool, we can clarify the current research trend and the cross-research between disciplines and even countries, which is significantly beneficial to the research progress of acupuncture treatment of pain, but there are still deficiencies. e literature selected in this paper is in English, while other languages are not included, which may lead to bias in some aspects.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the most effective drugs to relieve pain are opioids, and the most widely used drugs are nonsteroidal anti-inflammatory drugs (NSAIDs); at the same time, addiction, drowsiness, and other side effects could not be ignored [ 5 , 6 ]. Abuse of painkillers may cause serious damage to brain function [ 7 ]. The severe opioid crisis is a tough issue that deserves more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation intensity was adapted to the patient’s perception, at the limit of the pain threshold, and, if possible, provoking a motor reaction. These are the generally accepted parameters for optimal analgesia [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The choice of the acupuncture points was based on the fact that these points belong to a common set of analgesic acupuncture points, notably used in surgery, and frequently cited in publications in this context [ 25 , 26 , 27 , 42 , 43 ]. In addition to analgesia, their other potential actions are effects on the autonomic nervous system, in particular nausea and vomiting (Neiguan P 6), headaches (Hegu LI 4, Taichong LV 3), or sleep (Sanyinjiao SP 6).…”
Section: Methodsmentioning
confidence: 99%
“… 22 Acupuncture at P6 ( Neiguan ) acupoint significantly reduced the Visual Analog Scale pain score within 24–48 h in patients after craniotomy, reduced the incidence of vomiting within 24 h (the incidence rate in the acupuncture group is only 1/2 of that of the sham acupuncture group), and effectively prevented postoperative pain. 23 The study found that EA pretreatment at bilateral ST36 ( Zusanli ) acupoints significantly improved the intestinal function (the injury score of the EA pretreatment group is only 1/2 of that of the sepsis group) and survival rate (EA+Sepsis vs Sepsis: 75% vs 25%) in septic rats. 24 A randomized controlled trial showed that conventional therapies combined with EA at ST36 and ST37 ( Shangjuxu ) acupoints significantly reduced plasma level of TNF-α (from baseline 94.33±29.87 pg/mL to 19.68±11.70 pg/mL) and traditional Chinese medicine quantitative scores of intestinal dysfunction (from baseline 9.8±2.7 to 6.9±2.5) on day 7 in septic patients, and the effect of EA treatment group was better than that of conventional treatment alone.…”
Section: Introductionmentioning
confidence: 93%